PENINGKATAN HASIL BELAJAR SISWA DALAM OPERASI BILANGAN DENGAN MENGGUNAKAN GOOGLE MEET DI SEKOLAH DASAR - Nurul Adcha (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The Covid-19 pandemic disaster has affected various fields; one of which was the field of education. Starting from basic education to higher education, everything is hampered and cannot be carried out face-to-face because crowds can expand the spread of the Covid-19 virus. Utilizing google meet is believed to be a strategy to conduct online learning. Google meet allows teachers and students to make audiovisual calls in a classical form or in large numbers. In addition, this application provides many features that can support the implementation of online learning. This type of research was Classroom Action Research (CAR). This research used a research design model of Kemmis and Mc. Taggart referring to a spiral from one cycle to the next cycle. Each cycle included planning,, action, observation, and reflection (in Arikunto, 2002). Two cycles resulted in the increase of students’ learning outcomes from 60.45 to 80.45 with grades from 50 to 100. Thus, learning through google meet media was more effective in improving students’ learning outcomes in mathematical numbering operations.